Tourism Policy in the Czech Republic and the United Kingdom - Loyková, Markéta; Luštický, Martin, 1982-; Vysoká škola ekonomická v Praze. Fakulta managementu; Švanda, Pavel (2014)
The Bachelor thesis is focused on the issue of tourism policy and its application it two EU countries. It defines main attributes of tourism policy and pays special attention to tourism governance at national and regional level. The main aim of the thesis is to describe and compare systems of tourism policy in the Czech Republic and the United Kingdom. At the national level these systems are analysed from the point of view of tourism policy's goals, tools, main strategic documents and organizations involved in application of tourism policy. At regional level the thesis concentrates on destination management organizations (DMOs) which represent key players for successful implementation of tourism policy. It uses three attributes of the Stakeholder Circle Method for description of the relationship between two selected regional DMOs and their most important stakeholders
Vedoucí práce: Martin Luštický
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2014
Obsahuje bibliografii
Rok obhajoby 2014
Keywords: cestovní ruch; management destinací; politika cestovního ruchu; stakeholders; management [obor bakal. práce]; bakalářské práce; tourism; destination management; tourism policy; stakeholders; bachelor's theses